Detecting changes in land occupation and use (between 1984-2021) using "GEE" and GIS tools: focus on the green structure of the future metropolis of Annaba (north-east Algeria) - Noui, Nassira; Rouag Saffeddine, Djamila; Harizi, khaled (Indonesian Journal of Social Science Research, 2023)
Annaba, Algeria's fourth largest city, has acquired national and international importance due to its openness to the Mediterranean Sea. Over the last ten years, its rapid sprawl has continued to exacerbate the situation, leading to increased consumption of space, particularly green structures. The main objective of this study is to assess changes in land use and land cover (LULC) over the last 30 years, focusing on the green structure of the future metropolis. Google Earth Engine (GEE) was used to explore land cover classification using the random forest algorithm. A spatial model of the main changes in land cover between 1984, 2004 and 2021 was also generated. The principal drivers of land use change are human activities and urbanization, including fires and land clearing.The spatial pattern of change is mainly due to inappropriate investment policy and uncontrolled urbanisation. This is explained by the main results of the land use conversion processes between 1984 and 2021. The comparison shows a decline in forests and green land, mainly due to conversion to urbanised land, cropland, bare land or other land. Similarly, bare land and other types of land declined over the 1984-2004 period in favour of urbanised or cultivated land. Furthermore, it compromises any possibility of sustainable development at a time when we are facing climate change.